Double jeopardy: Comorbid obesity and cigarette smoking are linked to neurobiological alterations in inhibitory control during smoking cue exposure. (8th May 2019) - Ely, Alice V.; Jagannathan, Kanchana; Hager, Nathan; Ketcherside, Ariel; Franklin, Teresa R.; Wetherill, Reagan R.
Abstract: Obesity and cigarette smoking are two of the leading preventable causes of death in the United States. Research suggests that overlapping pathophysiology may contribute to obesity and nicotine use disorder (NUD), yet no studies have investigated the effect of obesity on neural response to reward stimuli in NUD. This study used arterial spin‐labeled perfusion functional magnetic resonance imaging (fMRI) to examine neural responses during exposure to smoking versus nonsmoking cues in 79 treatment‐seeking participants with NUD, 26 with normal weight, 28 with overweight, and 25 with obesity. Given that deficits in behavioral inhibitory control have been associated with both obesity and NUD, participants completed an affect‐congruent Go/NoGo task to assess the effect of body mass index (BMI) on this construct in NUD. Analyses revealed that BMI was negatively associated with activation in the right dorsolateral prefrontal cortex (dlPFC) in response to smoking cues, with significantly reduced response in smokers with overweight and smokers with obesity compared with normal‐weight smokers. In addition, greater commission errors on the Go/NoGo task were correlated with reduced neural response to smoking cues in the right dlPFC only among those with obesity. Together, these findings provide evidence that obesity in treatment‐seeking NUDs is related to neurobiological alterations in inhibitory control over cue‐potentiated behaviors, suggesting that smoking cessation may be more difficult in individuals with comorbid NUD and obesity than in those without, requiring treatment strategies tailored to meet their unique needs. Abstract : This study examined the effect of increasing body mass index (BMI) on brain response to smoking cues in nicotine use disorder (NUD) in 79 treatment‐seeking participants. Higher BMI was found to be related to lower activation in the right dorsolateral prefrontal cortex in response to smoking cues, and activation in this region was linked to performance on the Go/NoGo task, but only in obese participants. Findings suggest neurobiological alterations in inhibitory control in individuals with comorbid NUD and obesity.